Answer:
It would be shifted left.
Step-by-step explanation:
Let's call the two functions [tex]f(x)=x+2[/tex] and [tex]g(x)=x-1.[/tex] If you want a tranformation that maps f into g, you can see that you simply have to subtract 3 from f: in fact,
[tex]f(x)-2=(x+2)-3=x+2-3=x-1=g(x)[/tex]
Now, every transformation like [tex]f(x) { \to } f(x)+k.[/tex] results in a vertical translation, upwards if [tex]k>0[/tex] and downwards if [tex]k<0[/tex]. Since in our case [tex]k=-3,[/tex] the function is translated three units down.